Soziale Geschlechtergerechtigkeit in Wissenschaft und Forschung - Dahmen, Jennifer; Thaler, Anita (Verlag Barbara Budrich, 2017)
Under what conditions can gender equality and social gender justice in science and research in general be achieved? What concrete and effective measures are there to undermine some contrary practices? The book is aimed at practitioners and researchers alike who want to find out about known obstacles and how they can be circumvented as well as about the latest findings on European gender equality strategies.